Altered development of the brain after focal herpesvirus infection of the central nervous system - Koontz, Thad (The Rockefeller University Press, 2008)
Human cytomegalovirus infection of the developing central nervous system (CNS) is a major cause of neurological damage in newborn infants and children. To investigate the pathogenesis of this human infection, we developed a mouse model of infection in the developing CNS. Intraperitoneal inoculation of newborn animals with murine cytomegalovirus resulted in virus replication in the liver followed by virus spread to the brain. Virus infection of the CNS was associated with the induction of inflammatory responses, including the induction of a large number of interferon-stimulated genes and histological evidence of focal encephalitis with recruitment of mononuclear cells to foci containing virus-infected cells. The morphogenesis of the cerebellum was delayed in infected animals. The defects in cerebellar development in infected animals were generalized and, although correlated temporally with virus replication and CNS inflammation, spatially unrelated to foci of virus-infected cells. Specific defects included decreased granular neuron proliferation and migration, expression of differentiation markers, and activation of neurotrophin receptors. These findings suggested that in the developing CNS, focal virus infection and induction of inflammatory responses in resident and infiltrating mononuclear cells resulted in delayed cerebellar morphogenesis.